Odpowiedzi

Najlepsza Odpowiedź!
2009-12-16T12:55:37+01:00
=(16 1/2-13 7/9)*18/33+2 1/5*(8/33-1/11)+2/11
--------------------------------------------------------=
(6 3/4+5 1/2)*1/7-3/4

(15 27/18-13 14/18)*18/33+2 1/5*(8/33-3/33)+2/11
--------------------------------------------------------------=
(6 3/4+5 2/4)*1/7-3/4

2 13/18*18/33+2 1/5(5/33)+2/11
---------------------------------------=
11 5/4*1/7-3/4

49/18*18/33+11/5*5/33+2/11
----------------------------------=
49/4*1/7-3/4

49/33+11/33+2/11
-----------------------=
7/4-3/4
49/33+11/33+6/33
-----------------------=
4/4

66/33 2
-------=------=2*1 =2
1 1